Sistemas de riego en el rendimiento y rentabilidad de forraje hidropónico de Zea mays L. Zungarococha. Loreto - Pérez Sánchez, Dáney Fiorella (2025)
The research addresses the importance of optimizing agricultural production through efficient irrigation systems. The study focused on comparing the effects of hand irrigation and mist irrigation on the yield and economic profitability of hydroponic corn forage, an innovative technology that maximizes the use of limited resources such as water and space. The main objective was to determine the impact of irrigation systems on the productive yield and economic profitability of the crop. To do this, a completely randomized experimental design was used with two treatments (manual and nebulization irrigation) and 14 replications each, using hydroponic trays as experimental units. The data collected include yield in fresh and dry matter, production costs and income generated. The results showed that mist irrigation significantly outperformed manual irrigation, achieving an 8.7% increase in yield per tray and an economic profitability of 119.2%, compared to the 73.16% obtained with manual irrigation. In addition, the water and energy efficiency of the nebulization system was highlighted. It is concluded that mist irrigation is a superior alternative for the production of hydroponic corn forage in terms of yield and profitability. Its implementation in small and medium-scale agricultural systems is recommended, as well as the performance of additional studies to optimize its use in different agroclimatic conditions.